Molecular cloning, characterization and expression analysis of a novel PDRG1 gene from black tiger shrimp (Penaeus monodon) - Zhao,Chao (2017)
Abstract P53 And DNA Damage-Regulated Gene 1 (PDRG1) is a novel gene which plays an important role in chaperone-mediated protein folding. In the present study, the full-length complementary DNA (cDNA) sequence of the PDRG1 gene from Penaeus monodon (PmPDRG1) was cloned by the rapid amplification of cDNA ends (RACE) method. The cDNA of PmPDRG1 spans 1,613 bp, interrupted by only one short intron, and encodes a protein of 136 amino acids with calculated molecular weight of 15.49 kDa. The temporal expression profile of PmPDRG1 in different tissues and in different developmental stages of the ovary was investigated by real-time quantitative PCR (RT-qPCR). An RNA interference (RNAi) experiment was performed to study the relationship between P. monodon p53 (Pmp53) and PmPDRG1, and the results showed that the relative expression level of PmPDRG1 mRNA was notably up-regulated from 12 h to 96 h after Pmp53 was silenced both in ovary and hepatopancreas. To further explore the role of PmPDRG1 in ovarian development, dopamine (DA) and 5-hydroxytryptamine (5-HT)-injected shrimps were analyzed by RT-qPCR, indicating that PmPDRG1 may be involved in the regulation of ovarian development of P. monodon.